Place And Role of Civil Society Institutions in State And Community Management (The Peerian Journal, 2024)
This article explores the place and role of civil society institutions in the management of the state and society, the large-scale reforms implemented in our country, the construction of a democratic legal state and the development of a strong civil society, the role of democratic institutions in the formation and development of civil society